PENGEMBANGAN MEDIA BUSY BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AWAL DAN PERKEMBANGAN KOGNITIF ANAK USIA DINI (Studi Pada Anak Kelompok A PAUD Kota Bengkulu) - Nur Aprita; Nina Kurniah (DIADIK, 2021)
The purpose of this study was to produce a product in the form of busy book media as a learning medium to improve early reading skills and cognitive development as well as to determine the increase in early reading and cognitive development of children using developed busy book media compared to the learning media used by teachers. The subjects of this study were PAUD group A children, on a limited scale test the subject was PAUD IT Al Kahfi Bengkulu City, and on a wide scale test the subject was PAUD Islam Intan Insani Kota Bengkulu and PAUD IT IQRA in Bengkulu City. This research method is a research and development method (Research and Development -R & D-). Retrieval of research data using assessment sheets and observation sheets. The data collected in this study are data from media experts, data from material experts, and data from observations. The data analysis technique of the validation instrument used the mean score, the instrument analysis of reading ability and cognitive development used the percentage score and the different aspects of development using busy book media compared to LKA using the t-test. The results of this study indicate that the use of busy book media as a learning medium can improve children's early reading skills and cognitive development.